PENGARUH CITRA RESTORAN TERHADAP BEHAVIORAL INTENTION DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL MEDIASI (Survei pada Pelanggan Restoran di Seluruh Wilayah Kabupaten Karanganyar) - Suprihatmi Sri Wardiningsih, Rachmawan Rony Pradhana, Alwi Suddin & (Universitas Slamet Riyadi, 2017)
The objective of the research to analyses (1) effect of restaurant imageto behavioral intention, (2) effect of restaurant image to customer satisfaction,(3) effect customer satisfaction to behavioral intention, (4) effect of restaurantimage to behavioral intention, through customer satisfaction as the mediatingvariable. Population on this research are all customer of restaurant inKaranganyar. The samples of this research consist of 100 respondent, takenwith accidental sampling. To test the hypothesis, the researcher using thepath analysis. Result of this research reveals that (1) restaurant image havesignificance effect to behavioral intention; (2) restaurant image havesignificance effect to customer satisfaction; (3) customer satisfaction havesignificance effect to behavioral intention; (4) effect of restaurant image tobehavioral intention mediated by customer satisfaction. The conclusion ofthis research that all hypothesis are supported.Keywords: restaurant image, customer satisfaction, behavioral intentions